2019
DOI: 10.2298/abs181106012b
|View full text |Cite
|
Sign up to set email alerts
|

The response of weedy sunflower (Helianthus annuus L.) to nicosulfuron: An examination of vegetative parameters and acetolactate synthase activity

Abstract: Genetic and morphological interpopulation variability of weed species is often responsible for variable responses to herbicides. As weedy sunflower, an invasive form of Helianthus annuus L., possesses high morphological and genetic variability, very different responses of its populations to herbicides can be expected. This species is one of the dominant weed species in row crops, including maize, in many European countries in which nicosulfuron is intensively used for weed control. There are little available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
2
2
1
Order By: Relevance
“…Namely, the period between sowing and sampling dates in 2008 was characterized by somewhat higher rainfall than the corresponding period of 2009. This is coinciding with previous studies which confirmed that environmental conditions significantly affected the activity and effects of post-emergence herbicides (Bozic et al, 2012(Bozic et al, , 2015bBožić et al, 2019). In conclusion, nicosulfuron was found to have a significant impact on weedy sunflower vegetative production (plant height, fresh weight and leaf area) and on some generative parameters (number of heads per plant, weight of seeds per plant and number of seeds per plant).…”
Section: Methodssupporting
confidence: 90%
See 4 more Smart Citations
“…Namely, the period between sowing and sampling dates in 2008 was characterized by somewhat higher rainfall than the corresponding period of 2009. This is coinciding with previous studies which confirmed that environmental conditions significantly affected the activity and effects of post-emergence herbicides (Bozic et al, 2012(Bozic et al, , 2015bBožić et al, 2019). In conclusion, nicosulfuron was found to have a significant impact on weedy sunflower vegetative production (plant height, fresh weight and leaf area) and on some generative parameters (number of heads per plant, weight of seeds per plant and number of seeds per plant).…”
Section: Methodssupporting
confidence: 90%
“…Therefore, fresh weight and leaf area were more sensitive parameters (all applied herbicide rates reduced these parameters more than 50%) than plant height. This is not consistent with findings reported by Abbas et al (2005) that plant height was the more sensitive parameter to some ALS-inhibiting herbicides than dry weight, but it is in accordance with the findings of Božić et al (2019) who reported that plant height was the least sensitive parameter for estimating weedy sunflower response to nicosulfuron, compared to fresh weight and leaf area. Effects of herbicides (nicosulfuron in this case) to seed production of non-target weed species are important because seed production in a single growing season determines the potential weed problems in subsequent years.…”
Section: Methodscontrasting
confidence: 83%
See 3 more Smart Citations